Bcl-2 inhibitor uploaded upconversion nanophotosensitizers to overcome the photodynamic therapy resistance of cancer through adjuvant intervention strategy. (November 2017) - Liu, Xiaomin; Fan, Zhongqi; Zhang, Li; Jin, Zheng; Yan, Dongmei; Zhang, Youlin; Li, Xiaodan; Tu, Langping; Xue, Bin; Chang, Yulei; Zhang, Hong; Kong, Xianggui
Abstract: Similar to many other anticancer therapies, photodynamic therapy (PDT) also suffers from the intrinsic cancer resistance mediated by cell survival pathways. These survival pathways are regulated by various proteins, among which anti-apoptotic protein Bcl-2 plays an important role in regulation of programmed cell death and has been proved to involve in protecting against oxidative stimuli. Confronted by this challenge, we propose and validate here a novel upconversion photosensitizing nanoplatform which enables significant reduction of cancer resistance and improve PDT efficacy. The upconversion nanophotosensitizer contains the photosensitizing molecules - Zinc phthalocyanine (ZnPc) and Bcl-2 inhibitor - ABT737 small molecules, denoted as ABT737@ZnPc-UCNPs. ABT737 molecules were encapsulated, in a pH sensitive way, into the nanoplatform through Poly (ethylene glycol)-Poly (l -histidine) diblock copolymers (PEG- b -PHis). This nanosystem exhibits the superiority of sensitizing tumor cells for PDT through adjuvant intervention strategy. Upon reaching to lysosomes, the acidic environment changes the solubility of PEG-b-PHis, resulting in the burst-release of ABT737 molecules which deplete the Bcl-2 level in tumor cells and leave the tumor cells out from the protection of anti-apoptotic survival pathway in advance. Owing to the sensitization effect of ABT737@ZnPc-UCNPs, the PDT therapeutic efficiency of cancer cells can be significantly potentiated in vitro and in vivo .